Experimental infection of Klebsiella pneumoniae in urinary tract of rats and guinea pigs: Ibrahim Z.I and Alwaan M.J. - I., Ibrahim Z. (The Iraqi Journal of Veterinary Medicine, 2008)
This work aimed to study the pathological changes induced in theurinary organs after infection with K.pneumoniae. Two laboratory femaleanimal species ,white rat&guinea pig ,were infected by tworoutes,ascending (first group) and direct(intra renal-second group).The infection was examined in different periods through the bacterialculture of urine & kidney samples as well as the pathological changes(gross&microscopic) were examined after post mortum.The resultes of both groups showed a positive bacteriologic culture ofthe urine & kidney samples concomitant with the gross andhistopathological changes of the kidneys which revealed different degreesof inflammation between the two groups as well as within the indivisualsof the same group, especially the kidney specimens which showedpyelonephritis in rats & guinea pigs of both infection routes (ascendingand intrarenal